Assessment of effect of periodontal and prosthodontic therapy on glycemic control in patients with diabetes - Suman Bala (Wolters Kluwer Medknow Publications, 2021)
Background: Periodontitis is a chronic inflammatory disease of multifactorial etiology. The present study was conducted to assess the effect of periodontal and prosthodontic therapy on glycemic control in patients with diabetes. Materials and Methods: 80 type II diabetics patients of both genders were divided into Group I (periodontal and prosthodontic therapy) and Group II (Healthy). In control group, only oral hygiene instruction and mouth wash were prescribed. Results: Group I had 22 males and 18 females and Group II had 17 males and 23 females. The mean glycated hemoglobin level in Group I was 7.8% before and 6.7% after treatment and in Group II was 6.4% before and 6.2% after treatment. The difference was significant (P < 0.05). Conclusion: There was improvement in glycemic status in diabetic patients undergoing periodontal and prosthodontic therapy as compared to those not undergoing treatment.